Virtual Reality as A Digital Learning Innovation to Enhance the Skills of Students: A Systematic Review - Ruth Rize Paas Megahati S (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
A VR is a significant option for improving learning activities in schools, consistent with contemporary educational trends and technical progress. Prior studies reveal a deficiency in thorough assessments assessing VR as a digital learning innovation, particularly focused on improving student abilities. This study aims to analyze and highlight several research publications that examine virtual reality as a digital learning innovation to improve student skills. We chose the PRISMA diagram to conduct the systematic review process. Based on the established inclusion criteria, we identified 20 potential articles for the literature review. The selected articles emphasize the role of VR as a digital learning innovation aimed at enhancing student skills. VR is a promising digital learning innovation that can significantly enhance elementary school students' skills and engagement. This study collects and analyzes relevant research findings to conclude that VR is a digital learning tool for improve ESS skills. The implications of using VR in education are significant, offering opportunities to transform traditional learning environments and equip students with the skills needed for future success. However, careful consideration and strategic planning are essential to address the challenges and maximize the benefits of this innovative technology.